ORAL PROTOZOA ENTAMOEBA GINGIVALIS AND TRICHOMONAS TENAX AMONG PERIODONTITIS AND GINGIVITIS PATIENTS IN PERIODONTOLOGY DEPARTMENT DENTAL SECTION QUETTA - Abdul Samad Gichki; Maryam Mooen; Muhammad Tariq Hasni; Daud Ghilzi (Journal of Ayub Medical College Abbottabad, 2024)
Background: a group of eukaryotic organisms that are either free-living or parasitic and feed on organic matter, such as microorganisms or organic detritus. This group is referred to as a polyphyletic classification. They can be found in a wide variety of patterns and sizes, ranging from an amoeba, which can vary its shape, to a paramecium, which has a fixed shape and a complicated structure. The objective was to find out the occurrence of Entamoeba gingivalis and Trichomonas among Dental Patients visiting the Periodontology Department Dental Section, Sandeman, Provincial Hospital Quetta. Methods: The study design was randomized cross-sectional and conducted in the Department of Periodontology Dental Section, Sandeman Provincial Hospital Quetta, from March 2022 to February 2023. A total of 110 known cases of periodontitis and gingivitis were recruited in this study, and further to laboratory work the bacterial biofilm samples were collected from both gingivitis and periodontitis patients. The dental plaque was placed on individual glass microscope slides and a drop of saline and mixed and covered with a coverslip. The wet smear was examined immediately under 40X, and the objective for the presence and absence of motile amoebae or flagellated protozoa was recorded. Results: out of 110 known cases of periodontitis and gingivitis 91 (83%) patients were males and 19 (17%) were females among 110 patients, 40 (36%) patients were periodontitis and 70 (64%) patients were gingivitis. Among 40 (36%) periodontitis patients 3(7.5%) were Entamoeba gingivalis and 4(10%) were Trichomonas Tenax while 70 (64%) cases of Gingivitis 20 (28%) of Entamoeba gingivalis and 1(1%) Trichomonas tenax was recorded. No patient had both species of protozoa were seen in this study. Conclusion: The results of this study revealed the frequency of occurrence of E. gingivalis and T. tenax and the state of periodontitis and gingivitis. The prevalence of E. gingivalis was higher than T. tenax. We recommended further research with a higher number of patients and may use more advanced and reliable laboratory techniques such as PCR and electron microscopy.